Analysis of Marketing Mix In Enhancing The Marketing Of UMKM Kue Podeng Enin, Tigaraksa District, Tangerang Regency - Jaka Slameta; Bagus Dirgantoro; Aries Setiawan; I Gusti Birawan; Sumardi Sumardi (The International Journal of Education Management and Sociology, 2025)
Kue Podeng is a traditional cake made from wheat flour, grated coconut, and sugar. It is relatively simple to prepare: the mixed dough is poured into molds and cooked until done. This culinary product is well known among the residents of Tigaraksa, Tangerang Regency, as it is an original local delicacy that has been around for decades. Currently, the business is managed by the third generation of the family. In terms of taste, kue podeng is sweet with a soft texture, and its price remains highly affordable for the local community. Despite being the only business that produces and sells this product in the area, the development of the kue podeng micro, small, and medium enterprise (UMKM) appears stagnant. Like all business actors—whether on a small or large scale the goal is to grow the business and generate profit, which ultimately contributes to the welfare of the entrepreneurs. This study aims to examine strategies to improve the marketing of this UMKM through a detailed analysis using the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence). The research is based on qualitative data collected through field interviews and observations. The findings are expected to provide significant contributions to the marketing development of Kue Podeng Enin and offer valuable insights for stakeholders, including UMKM actors, the government, investors, and the broader community. This research is categorized as field research, where data is collected directly from the site by observing various relevant issues. The study was conducted at UMKM Kue Podeng Enin, located in Tigaraksa District, Tangerang Regency. Data collection methods included field observation, interviews, and documentation, with interviews serving as the primary research instrument.